Protein‐enriched soup and weekly exercise improve muscle health: A randomized trial in mid‐to‐old age with inadequate protein intake - Li‐Ning Peng; Ming‐Hsien Lin; Sung‐Hua Tseng; Ko‐Han Yen; Huei‐Fang Lee; Fei‐Yuan Hsiao; Liang‐Kung Chen (Wiley, 2024)
Abstract Background Prior research has highlighted the synergistic impact of protein supplementation on muscle function post‐exercise in adults; however, evidence supporting the combined effects were less robust and inconsistent on those with protein insufficiency. This investigation aims to explore efficacy of protein‐enriched soup coupled with exercise on muscle health and metabolism in middle‐aged and older adults with suboptimal protein intake. Methods An open‐label, 12‐week, randomized controlled trial involving participants with insufficient protein intake (<1.0 g/kg/day) was done. The intervention group consumed protein‐enriched soup (24-30 g protein daily) and 1‐h weekly exercise, while controls received health education. Assessments included laboratory tests, functional assessments, and body composition. Results In this trial, 97 out of 100 randomized participants (mean age: 64.65 ± 4.84 years, 81.8% female) completed the study (47 in intervention group and 50 in control group). Compared results of baselines, at 1 and 3 months of intervention, significant improvements in waist circumference (83.48 ± 10.22 vs. 82.5 ± 9.88 vs. 82.37 ± 9.42 cm, P for trend = 0.046), 6‐min walking distance (525.65 ± 58.46 vs. 534.47 ± 51.87 vs. 552.02 ± 57.66 m, P for trend = 0.001), five‐time sit‐to‐stand time (7.63 ± 1.63 vs. 6.81 ± 1.8 vs. 6.4 ± 1.42 s, P for trend <0.001), grip strength (26.74 ± 6.54 vs. 27.53 ± 6.99 vs. 28.52 ± 7.09 kg, P for trend <0.001), and MNA score (26.8 ± 2.14 vs. 27.73 ± 1.74 vs. 27.55 ± 1.72, P for trend <0.001) were discerned within the intervention group. The intervention demonstrated a significant reduction in serum triglyceride (105.32 ± 49.84 vs. 101.36 ± 42.58 vs. 93.43 ± 41.49 mg/dL, P for trend = 0.023), increased HDL‐C (60.04 ± 16.21 vs. 60 ± 17.37 vs. 62.55 ± 18.27 mg/dL, P for trend = 0.02), and DHEA‐S levels (97.11 ± 54.39 vs. 103.39 ± 56.75 vs. 106.83 ± 60.56 μg/dL, P for trend = 0.002). Serum myostatin did not differ in both groups, but serum leptin levels significantly increased (9118.88 ± 5811.68 vs. 11508.97 ± 7151.08 vs. 11220.80 ± 7190.71 pg/mL, P for trend = 0.016) in controls. The intervention group showed greater improvements in 6 min walking distance (β = 0.71, 95% CI: 6.88 to 40.79, P = 0.006), five‐time sit‐to‐stand test (β = −0.87, 95% CI: −1.59 to −0.15, P = 0.017), MNA score (β = 0.96, 95% CI: 0.20 to 1.71, P = 0.013), serum triglycerides (β = −15.01, 95% CI: −27.83 to −2.20, P = 0.022), LDL‐C (β = −9.23, 95% CI: −16.98 to −1.47, P = 0.020), and DHEA‐S levels (β = 9.98, 95% CI: 0.45 to 19.51, P = 0.04) than controls. Conclusions Protein‐enriched soup with weekly exercise over 12 weeks significantly improved physical performance, lipid profile, and DHEA‐S levels among middle‐aged and older adults with inadequate protein intake, while studies assessing long‐term benefits of the intervention are needed.